2012
DOI: 10.2174/156652412803833508
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol: A Novel Natural Agent for Cancer Prevention and Therapy

Abstract: Honokiol ((3’,5-di-(2-propenyl)-1,1’-biphenyl-2,2’-diol) is a bioactive natural product derived from Magnolia spp. Recent studies have demonstrated anti-inflammatory, anti-angiogenic, anti-oxidative and anti-cancer properties of honokiol in vitro and in preclinical models. Honokiol targets multiple signaling pathways including nuclear factor kappa B (NF-κB), signal transducers and activator of transcription 3 (STAT3), epidermal growth factor receptor (EGFR) and mammalian target of rapamycin (m-TOR), which have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
178
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(185 citation statements)
references
References 69 publications
7
178
0
Order By: Relevance
“…In 2012, the World Health Organization (WHO) recorded 14 million new cases of cancer and 8.2 million cancer-related deaths, with 4.3 million under the age of 70 years (WHO, 2016). Significant progress in the fight against cancer still calls for both advances in cancer diagnosis and development of preventive and therapeutic strategies (Arora et al, 2012). Herbal therapies from alternative and complementary medicines may hold a key to such advances; for example, TCM proposes preparations to treat cancers, but the effective component(s) or their mode of action at cellular and molecular levels is largely unknown (Yang et al, 2003).…”
Section: Cytotoxic Activity: Eventual Therapeutic Application In Cancer?mentioning
confidence: 99%
See 2 more Smart Citations
“…In 2012, the World Health Organization (WHO) recorded 14 million new cases of cancer and 8.2 million cancer-related deaths, with 4.3 million under the age of 70 years (WHO, 2016). Significant progress in the fight against cancer still calls for both advances in cancer diagnosis and development of preventive and therapeutic strategies (Arora et al, 2012). Herbal therapies from alternative and complementary medicines may hold a key to such advances; for example, TCM proposes preparations to treat cancers, but the effective component(s) or their mode of action at cellular and molecular levels is largely unknown (Yang et al, 2003).…”
Section: Cytotoxic Activity: Eventual Therapeutic Application In Cancer?mentioning
confidence: 99%
“…Studies in in vitro and animal models have shown that Magnolia components, especially the neolignans honokiol and magnolol, are able to target many pathologically relevant pathways (Arora et al, 2012). These findings have increased interest in using neolignans as possible novel chemotherapeutic agents; notably, mechanistic studies have been carried out on honokiol to assist the development of novel synthetic analogues and to provide clues for rational combinations with conventional chemo-or radiotherapy (Fried and Arbiser, 2009).…”
Section: Cytotoxic Activity: Eventual Therapeutic Application In Cancer?mentioning
confidence: 99%
See 1 more Smart Citation
“…Honokiol started to capture attention in recent 20 years mainly because of the finding of its promising therapeutic potential to treat multiple human diseases (especially for tumour and thrombus) (Fukuyama et al 2002; Hu et al 2005; Arora et al 2012). Compared with the gradually accumulated knowledge from clinical applications, nevertheless, the understanding of the honokiol’s mode-of-action (MoA) at the molecular levels still remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Honokiol (HNK), a small molecular weight natural product derived from the stem and bark of the plant Magnolia officinalis (Fried and Arbiser 2009), has been reported to possess potent anti-neoplastic and anti-angiogenic properties through targeting multiple signaling pathways including PI3K/Akt, STAT3, nuclear factor-kappa B (NF-kappaB), epidermal growth factor receptor (EGFR), and mammalian target of rapamycin (m-TOR) (Arora et al 2012). For example, HNK induced G1 cell cycle arrest and apoptosis by reducing the expression of cyclins D, cellular inhibitor of apoptosis 2 (cIAP2), X-linked inhibitor of apoptosis protein (XIAP), and survivin in adult T-cell leukemia (Ishikawa et al 2012).…”
Section: Introductionmentioning
confidence: 99%